Maternidade na adolescência : efeitos a curto e longo prazo sobre a saúde e o capital humano dos filhos. Coortes de Nascimentos de Pelotas, RS - 1982, 1993 e 2004 - Restrepo Méndez, María Clara (2012)
Although adolescent fertility rates are decreasing worldwide, adolescent childbearing keeps its visibility as a social phenomenon that needs special attention by policy makers and researchers. Many studies suggest that being a teenage mother have deleterious effects for her own health and her child s health during the first years of life. Other authors point out that teenage childbearing also had long-term consequences; however, the literature in this regard is limited, particularly in low and middle income countries. The 1982, 1993 and 2004 Pelotas birth cohorts provided a valuable opportunity to study the short and long-term consequences of adolescent childbearing on several offspring outcomes relate to health, behavior, education and employment. The hypothesis of an increased risk of death during the fetal, perinatal, neonatal, post-neonatal and infant periods among offspring of adolescent mothers was tested in all three cohorts. Additionally, we tested hypotheses regarding the long-term consequences on offspring, including health-related behaviors, sexual activity, education and employment in adolescents and young adults. Our results showed a greater likelihood of post-neonatal mortality among offspring of adolescent mothers after adjustment for confounders. However, this effect disappeared after controlling for factors such as weight gain during pregnancy and antenatal care. Moreover, children of teenage mothers were more likely to initiate sexual intercourse before age 16, to be themselves teenage parents, and to begin family formation earlier. On balance, the results from both Pelotas cohort studies and a systematic review of the literature suggest that pre-gestational socioeconomic and family characteristics explained most of the adverse events observed in children. Therefore, programs for prevention of adolescent childbearing should target to change the circumstances surrounding teenage mothers, such as low education and poverty, because these remain the most important predictors of the disadvantage conditions of their offspring in relation to health and socioeconomic characteristics.